Correction of physical education program for technical higher educational establishment girl-students on the base of their health indicators - A.N. Kolumbet; L.Yu. Dudorova (Physical Education of Students, 2016)
Purpose: to illustrate opportunities of physical education in health strengthening of technical HEE girl-students through correction of their biological age components. Material: 127 girl-students participated in the research. Results : the authors’ program of biological age correction permitted to increase breathing pauses, hand strength, time of static balance and reduce blood pressure. Knowledge of biological age and mechanisms of too early ageing facilitates practicing healthy life style and formation of body-motor conditions. We offered trainings of biological age correction’ methodic, oriented on prophylaxis of organism’s ageing, reduction of biological age and prolongation girl-students’ active life. Conclusions: specially determined biological age of an individual can be used as integral characteristic of his/her health condition.